‘Am I fixed, am I better now?’: undergoing MR-guided focused ultrasound for essential tremor: an interpretative phenomenological analysis - Stoycheva, Tsvetina; Jameel, Ayesha; Bain, Peter; Nandi, Dipankar; Jones, Brynmor; Honeyfield, Lesley; Gedroyc, Wladyslaw; Moore, Jaqualyn (Frontiers in Neurology, 2024)
Essential tremor (ET) is characterised by postural and intentional tremor typically affecting the upper limbs, which can negatively impact functionality and quality of life. Magnetic Resonance-guided Focused Ultrasound (MRgFUS) is a novel and promising non-invasive treatment for ET which offers instantaneous results. Using interpretative phenomenological analysis we explored the experience of undergoing MRgFUS in six ET patients as well as their experiences pre-and post-procedure. Onetime, retrospective semi-structured interviews were conducted and six themes emerged: Life pretreatment: "It's everyday tasks that get you down" and "Most people who understand, they are okay. Some people aren't"; MRgFUS: Treatment day: "Going into the unknown" and "There's no way I was going to press that button"; and Life post-treatment: "One is good. Two is better" and "Am I fixed, am I better now?". The findings point to a significant period of adjustment associated with living with ET and the effects of undergoing ET MRgFUS treatment. As ET progressed, participants struggled to cope with increasing symptoms and had to develop coping strategies to manage life with ET. The procedure itself was perceived as strange and extraordinary and despite some immediate adverse effects participants were determined to go through with it. Post procedure, all participants reported tremor suppression which was life changing. While some participants still felt burdened by ET, others expressed it took them a while to psychologically adjust to what essentially was their new body. This study has highlighted the need for patients to be supported at all stages of their ET journey.